Modelling and control of self-service public bicycle systems by using Petri nets. (15th October 2012) - Benarbia, Taha; Labadi, Karim; Darcherif, Abdel Moumen; Chayet, Maurice
In recent years, self-service public bicycle systems (SPBS) are available in numerous big cities in the world (Vélib' in Paris, Bicing in Barcelona, Call-a-bike in Munich, Oybike in London …). As a new public transportation mode, bicycle use entails a number of benefits including environmental, mobility and economic benefits. In this paper, we develop an original Petri net approach for SPBS modelling and performance evaluation for control purposes. A modular framework based on Petri nets with marking dependent weights is proposed and a simulation software tool is developed and used to simulate and validate models described in this paper. Our approach is intended to help planners and decision makers in determining how to implement, and operate successfully these complex dynamical systems.